THE UNION OF GOD: UNDERSTANDING THE CONCEPT OF THE HOLY SPIRIT IN CATHOLICISM - Maufur, Maufur (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2017)
During this time Trinitias is widely misunderstood by Muslims as a form of polytheism. The Trinity is assumed to be three distinct entities: God the Father, Lord the Son, and the Holy Spirit. This paper seeks to examine the dogma of the Holy Spirit as one element of the Trinity. This paper concludes that in Catholic, the Holy Spirit is the unity of the Father and the Son in the form of Love that is near in the created universe. The Holy Spirit is also God and is equal to the fi rst and second person of God, and therefore His presence as commanded by God does not mean that He is inferior to the other two. The presence of the Holy Spirit in this world means the salvation, liberation, and existence of the Christian community (ie followers of Jesus) who came to be known as the Church. Keywords: Trinity, Holy Spirit, Catholicism